Enhancing Interferometer Sensitivity Using Kerr Squeezing in Fibers - Kalinin, Nikolay; Dirmeier, Thomas; Sánchez-Soto, Luis L.; Leuchs, Gerd; Andrianov, Alexey V. (Quantum 2.0: Proceedings Optica Quantum 2.0 Conference and Exhibition, 2023)
We present an all-fiber robust setup for polarization squeezing generation using the Kerr effect in fibers. For the first time, a third-order nonlinearity is used to demonstrate interferometer sensitivity enhancement beyond the shot noise limit.
CRIS-Team Scopus Importer:2024-12-16